Trio, a Rho Family GEF, Interacts with the Presynaptic Active Zone Proteins Piccolo and Bassoon. - Ryan T Terry-Lorenzo; Viviana I Torres; Dhananjay Wagh; Jose Galaz; Selene K Swanson; Laurence Florens; Michael P Washburn; Clarissa L Waites; Eckart D Gundelfinger; Richard J Reimer; Craig C Garner (PLoS ONE, 2016)
Synaptic vesicles (SVs) fuse with the plasma membrane at a precise location called the presynaptic active zone (AZ). This fusion is coordinated by proteins embedded within a cytoskeletal matrix assembled at the AZ (CAZ). In the present study, we have identified a novel binding partner for the CAZ proteins Piccolo and Bassoon. This interacting protein, Trio, is a member of the Dbl family of guanine nucleotide exchange factors (GEFs) known to regulate the dynamic assembly of actin and growth factor dependent axon guidance and synaptic growth. Trio was found to interact with the C-terminal PBH 9/10 domains of Piccolo and Bassoon via its own N-terminal Spectrin repeats, a domain that is also critical for its localization to the CAZ. Moreover, our data suggest that regions within the C-terminus of Trio negatively regulate its interactions with Piccolo/Bassoon. These findings provide a mechanism for the presynaptic targeting of Trio and support a model in which Piccolo and Bassoon play a role in regulating neurotransmission through interactions with proteins, including Trio, that modulate the dynamic assembly of F-actin during cycles of synaptic vesicle exo- and endocytosis.